The magic princess dress - Rees, Gwyneth; Eckel, Jessie (London macmillan children's book, 2010)
When Ava enters Marietta's dress shop on the hunt for her missing cat, she has no idea how magical it will be. Soon Ava is trying on a beautiful dress, only to be whisked away to Fairytale Land - where Cinderella is about to get married, and her Fairy Godmother is about to turn Ava's cat into something a lot less cute and fluffy
English Stories
Keywords: English stories